2003
DOI: 10.22358/jafs/67642/2003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selected rumen fauna on fibrolytic enzyme activities, bacterial mass, fibre disappearance and fermentation pattern in sheep

Abstract: Three Polish Merino wethers, fed hay and ground barley, were defaunated and then faunated with Eudiplodinium maggii only; with Eudiplodinium maggii and Entodinium caudatum or with both opryoscolecids and Dasytricha ruminantium. The total number of ciliates varied in the range of 16-403 x 10 3 /g rumen content depending on the experimental period. Total bacterial contributed to 12.7-19.6% DM of rumen digesta. The bacterial matter in two of three sheep was negatively influenced by Entodinium caudatum and Dasytri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 8 publications
2
19
1
Order By: Relevance
“…The higher activity of xylanase in animals fed live yeast agrees with results published by Michalet- Doreau et al (1997). It can not be precluded that the increase in fibrolytic activity could result from the increase in the number of cellulolytic ciliates from the genus Diplodinium, for example, Eudiplodinium maggii, Diploplastron affine and Anoplodinium denticulatum, which were present in the rumen of goats and which exhibit high cellulolytic and xylanolytic activity (Michałowski et al, 2003;Stan et al, 2006). In the present study it was found that the amylolytic activity in the rumen decreased significantly when the control diet fed to the goats was replaced by the ration supplemented with live yeast (Table 3).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The higher activity of xylanase in animals fed live yeast agrees with results published by Michalet- Doreau et al (1997). It can not be precluded that the increase in fibrolytic activity could result from the increase in the number of cellulolytic ciliates from the genus Diplodinium, for example, Eudiplodinium maggii, Diploplastron affine and Anoplodinium denticulatum, which were present in the rumen of goats and which exhibit high cellulolytic and xylanolytic activity (Michałowski et al, 2003;Stan et al, 2006). In the present study it was found that the amylolytic activity in the rumen decreased significantly when the control diet fed to the goats was replaced by the ration supplemented with live yeast (Table 3).…”
Section: Resultssupporting
confidence: 89%
“…In our experiment, the total number of protozoa did not change after enrichment of the control diet with live yeast, but a numerical increase in the population density of ciliates from the genus Diplodinium was observed (Table 2). It is well known that some species from this group are characterized by high cellulolytic and, especially, xylanolytic activity (Michałowski et al, 2003;Stan et al, 2006). Our results thus support the suggestion of the authors cited above but contradict the results of Arcos-García et al (2000) who did not observe increased digestibility of cell wall carbohydrates in the rumen when fungal preparations were added to the ration.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This finding suggests a negative effect of Saccharomyces cerevisiae on the activity and/or number of fibrolytic species of ruminal microorganisms, but not on the digestibility of fibrous nutrients (Michałowski et al, 2003). It was found that the activity of CMC-ase and xylanase decreased after feeding and then increased and that the yeast did not affect the pattern of these changes.…”
Section: Resultsmentioning
confidence: 90%
“…The live yeast cells added to the ruminants' diets could increase the activity of cellulase because they stimulated the activity of cellulolytic bacteria, in particular of Fibrobacter succinogenes, Ruminococcus albus, as well as Ruminococcus flavefaciens (Chaucheyras et al, 1997). It can not be precluded that the increase in cellulolytic activity could result from an increase in the number of cellulolytic protozoa from the genus Diplodinium, e.g., Eudiplodinium maggii and Diploplastron affine, which are commonly present in the rumen of domestic ruminants (Michałowski et al, 2003). The authors found that up to 38% of total cellulolytic activity in the rumen originated from Eudiplodinium maggii, and that this contribution was visibly related to the number of ciliates.…”
Section: Resultsmentioning
confidence: 99%